Determinants of Capital Structure in Indian Public Ltd. Companies: An Experience of Pre and Post Liberalization - Srivastava, Ankita (Indian Journal of Finance, 2012)
The present study has two objectives: Firstly, to identify important determinants of capital structure and secondly, to verify for the applicability of trade-off and pecking order theory. The period of study is from 1977-78 to 2006-2007, which has been divided into two equal halves designated as pre and post liberalization for better understanding. Data for the present study comprises of consolidated sources and uses of funds of Indian Public Limited companies obtained from various issues of RBI bulletin. Capital structure, the dependent variable, is considered in two forms viz., total debt to total assets and long-term debt to total assets. Six explanatory variables are firm size, asset structure, non-debt tax shield (NDTS), cash, growth opportunities and profitability. The explanatory power of the model measured in terms of R2 in the total time period is 62% and 66% for total debt and long-term debt respectively. Once the study period is divided into pre and post liberalization, a dramatic change occurred in the explanatory power as the value ofÂ R2 is 93% and 98% for the same variable in the pre liberalization period and 86 % and 80% for post liberalization. Similarly, the significance of variables changed in different time periods. It shows that variables have varied importance in various time periods. It is confirmed by chow test. The regression analysis suggests applicability of both the theories.